2017
DOI: 10.1371/journal.pone.0180157
|View full text |Cite
|
Sign up to set email alerts
|

Metal contamination in harbours impacts life-history traits and metallothionein levels in snails

Abstract: Harbours with limited water exchange are hotspots of contaminant accumulation. Antifouling paints (AF) contribute to this accumulation by leaching biocides that may affect non-target species. In several leisure boat harbours and reference areas in the Baltic Sea, chronic exposure effects were evaluated using caging experiments with the snail Theodoxus fluviatilis. We analysed variations in ecologically relevant endpoints (mortality, growth and reproduction) in concert with variation in metallothionein-like pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
1
9
1
1
Order By: Relevance
“…They were partly higher than concentrations of the IKSR monitoring (0.77 −2.4 µg/L Cu and < 1−5.3 µg/L Zn; IKSR/CIPR/ICBR 2018), which could be due to the fact that sites with a potential higher metal exposure, like marinas or industrial harbours, were selected. Furthermore, both copper and zinc concentrations in our study were at individual sites higher than concentrations found in a comparable study in Swedish harbours leading to higher mortality, reduced growth, and lower fecundity of the brackish water form of T. fluviatilis (2.7−3.7 µg/L Cu and 7.1−10.6 µg/L Zn; Bighiu et al 2017). Given our results showing no significant effects of detected copper and zinc concentrations on population and histopathological parameters of the Danubian form of T. fluviatilis in the field, it can be presumed that the cryptic invader is able to cope with concentrations of these metals at the examined sites.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…They were partly higher than concentrations of the IKSR monitoring (0.77 −2.4 µg/L Cu and < 1−5.3 µg/L Zn; IKSR/CIPR/ICBR 2018), which could be due to the fact that sites with a potential higher metal exposure, like marinas or industrial harbours, were selected. Furthermore, both copper and zinc concentrations in our study were at individual sites higher than concentrations found in a comparable study in Swedish harbours leading to higher mortality, reduced growth, and lower fecundity of the brackish water form of T. fluviatilis (2.7−3.7 µg/L Cu and 7.1−10.6 µg/L Zn; Bighiu et al 2017). Given our results showing no significant effects of detected copper and zinc concentrations on population and histopathological parameters of the Danubian form of T. fluviatilis in the field, it can be presumed that the cryptic invader is able to cope with concentrations of these metals at the examined sites.…”
Section: Discussioncontrasting
confidence: 81%
“…However, one must also consider the enormous variability of effects of not only metals, but also other environmental pollutants, across metals and invertebrate taxa. Snails have various detoxification mechanisms to counteract metal toxicity and reduce their bioavailability (Bighiu et al 2017 ; Mahmoud and Abu Taleb 2013 ; Watermann et al 2008 ), which is not the case for several other sensitive taxa. The knowledge of effects on a chosen species is essential for environmental monitoring, but concentrations should be compared considering the whole variety of invertebrate species, also taking the transfer of metals along food chains and the community level into account (Rainbow 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…These ranges are similar to those of the two marinas in this study, with measured peak season ranges of 2.6-3.5 μg Cu/L and 5.0-9.8 μg Zn/L. In Baltic Sea field experiments, similar concentrations of Cu and Zn were strongly correlated to increased mortality and reduced reproduction in exposed organisms (Bighiu et al 2017a(Bighiu et al , 2017b.…”
Section: Comparison With Other Marinas and Eqs Valuessupporting
confidence: 86%
“…Marine ecosystems are the final receptacle of contaminants released to the environment, especially in seaports and other industrialized or strongly anthropised coastal areas. Boat harbours, for instance, may be hotspots of contaminant accumulation (Bighiu et al, 2017;Johnston et al, 2011). Indeed, they are likely to receive both a cumulative load of pollutants from upstream point and nonpoint sources from watershed, and many pollutants generated at the marina itself.…”
Section: Introductionmentioning
confidence: 99%
“…This often results in greater impacts in the area concerned on ecological communities (Sim et al, 2015). Because of their environmental persistence, heavy metals are one of the major harmful toxic pollutants for the marine environment (Stankovic et al, 2014) and especially in harbours and marina (Bighiu et al, 2017;Galkus et al, 2012). The major proportion of these trace elements is trapped in coastal sediments where they can be continuously released into the water column and incorporated into food webs.…”
Section: Introductionmentioning
confidence: 99%